Biomass and nutrients in different compartments above ground of Mimosa velloziana Mart and Tephrosia candida D.C. species - Caldeira, Marcos Vinicius Winckler; Sperandio, Huezer Vigano; Delarmelina, William Macedo; Burak, Diego Lang; Hunz, Sustanis Horn (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
The recovery of a degraded area is to make it productive again, either for conservation or production, it is necessary to generate knowledge related to technical procedures. Thus, this study aimed to evaluate the biomass and nutrient concentrations in different compartments above the ground, in two legume species (Mimosa velloziana Mart and Tephrosia candida DC). The Legumes are established under Udult Distrocoeso in Linhares, ES. The legume biomass above ground was separated into the components leaves, living branches and dead branches and leaves for Mimosa, and branches with a diameter less than 2 cm, and dead branches, for “Tefrósia”. With dry samples and ground aerial biomass of legumes, proceeded to the chemical analysis of nutrients. After analysis, it was found that the “Tefrósia” showed the highest production of aboveground biomass, being in the leaves, the highest concentrations of nutrients. The Tephrosia candida and Mimosa velloziana species have potential for inclusion in projects and recovery of degraded areas or for green manure. There was a higher nutrient content in “tefrósia”, depending on its larger and consequently higher biomass. The highest concentrations of nutrients were found in the leaves of both pulses, confirming the potential of this organ in nutrient cycling.